Blastogenic Responses of Human Gingival Lymphocytes to Mitogens - YAMASHITA, Kaoru (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 1985)
The purpose of the present study was to evaluate the blastogenic responses of gingival lymphocytes stimulated by phytohemagglutinin (PHA), concanavalin A (Con A) and pokeweed mitogen (PWM) in human periodontal disease. And then, the differences between the gingival lymphocyte and peripheral blood lymphocyte (PBL) response were examined. Gingival tissues were obtained during periodontal surgery or extraction from seven patients, who included four patients with adult periodontitis (AP), and three with rapidly progressive periodontitis (RPP). Gingival lymphocytes and PBLs were isolated by collagenase treatment and Ficoll-gradient procedure. Viable cells (2×105) from gingival lymphocytes and PBLs were suspended in each well of microcultureplate and maintained in RPMI 1640 containing 10% fetal calf serum. The microcultures were stimulated by optimal dose of PHA (10μg/ml), Con A (5μg/ml) and PWM (10μg/ml) and incubated for 96h at 37°C in a humid 95% air and 5% CO2 environment. Tritiated thymidine (0.5μCi) was added to each well 24h before harvesting for measurement of DNA synthesis. The response of stimulated and unstimulated gingival lymphocytes was low as compared with PBLs. The activity of PBL unstimulated culture in RPP was lower than that of AP. But the CPM of PHA stimulated PBLs in RPP was similar to that of AP. The response of gingival lymphocytes in unstimulated cultures was the same level between AP and RPP, while the activity of PHA stimulated gingival lymphocytes in RPP was higher than that of AP.